Legislation on Social Partnership in the Eurasian Economic Union: Legal Framework and Development Prospects (EUROPEAN AND ASIAN LAW REVIEW, 2025)
It is impossible to imagine social and labor relations without a developed social partnership. The process of radical reorientation of public life in the country has affected almost all sectors of the economy. Scientific and technological progress requires employers to innovate in means of production, technologies and labor organization. In this regard, the state should promote further harmonization of social and labor relations by effectively protecting the laborrights of employees. This publication discusses the idea of creating a unified legal framework for social partnership in the field of labor in the EAEU (Eurasian Economic Union) space. The necessity of detailed regulation of the principles of the organization of socio-economic systems is substantiated, since the consistent and phased implementation of uniform labor standards is the most important task of harmonious development.
Keywords: social partnership; social dialogue; Eurasian Economic Union; labor legislation